Studi Eksegesis Kisah Para Rasul 19:2a “Sudahkah Kamu Menerima Roh Kudus, Ketika Kamu Menjadi Percaya?” - Bobo, Kornelis Ruben (LOGIA: Jurnal Teologi Pentakosta, 2023)
Abstraksi:Karya tulis ini merupakan suatu studi ekesegesis terhadap Kisah Para Rasul 19:2a, yang berbunyi, “Sudahkah kamu menerima Roh Kudus, ketika kamu menjadi percaya?”  Tujuan utama penulisan karya tulis ini adalah untuk mengetahui apakah pengalaman “menerima Roh Kudus terjadi seketika itu juga waktu seseorang menjadi percaya kepada Yesus (bersamaan)?  Atau justru sesuatu pengalaman yang langsung mengikuti setelah seseorang menjadi percaya kepada Yesus?  Atau ada selang beberapa waktu kemudian setelah seseorang menjadi percaya kepada Tuhan Yesus?  Proses penulisan karya tulis ini akan menggunakan studi pustaka secara eksegetikal - historikal.  Setelah mengerjakan karya tulis ini, ditemukan bahwa pengalaman menerima Roh Kudus terjadi setelah seseorang menjadi percaya kepada Tuhan Yesus.  Jadi, pengalaman menerima Roh Kudus merupakan sesuatu pengalaman yang mengikuti setelah seseorang menjadi percaya kepada Tuhan Yesus.  Hanya, tidak dapat dipastikan apakah pengalaman itu sesuatu yang langsung terjadi atau masih dalam beberapa waktu kemudian setelah seseorang menjadi percaya kepada Tuhan Yesus.  Namun, berdasarkan studi eksegesis, pengalaman menerima Roh Kudus terjadi setelah (bukan bersamaan - ketika) seseorang menjadi percaya kepada Tuhan Yesus.  Jadi, jika kita terjemahkan Kisah Para Rasul 19:2a akan berbunyi demikian, “Dan dia [Paulus] berkata kepada mereka [beberapa orang murid]: apakah kamu sekalian telah menerima Roh Kudus,  [sesudah] kamu sekalian sungguh-sungguh percaya?   AbstractThis paper is an exegetical study of Acts 19:2a, which reads, "Have you received the Holy Spirit when you believed?" There is one reason why this text needs to be studied, namely the absence of the word "when" in the Greek text. While the LAI, NIV (New International Version), NASB (New American Standard Bible), RSV (Revised Standard Version) translate with when (when, when, when). However, there are also some English Bibles such as the KJV (Kings James Version), WBT (Webster's Bible Translation) which translate with since (since, after, after). This difference in translation makes us ask what the translation of the original Greek text actually sounds like. A further question, after knowing the original Greek text, is whether the experience of receiving the Holy Spirit occurs when someone believes in Jesus (at the same time - right away) or is it an experience that occurs after someone believes in Jesus. Through writing this paper, it can be seen whether the experience of "receiving the Holy Spirit occurs immediately when a person believes in Jesus (simultaneously)? Or is it actually an experience that immediately follows after someone believes in Jesus? Or does it take some time after someone believes in the Lord Jesus? Writing this paper will use qualitative methods. After completing this paper, it was discovered that the experience of receiving the Holy Spirit occurs after a person believes in the Lord Jesus. The experience of receiving the Holy Spirit is an experience that follows after a person believes in the Lord Jesus. However, it cannot be ascertained whether the experience was something that happened immediately or some time later after someone believed in the Lord Jesus. However, based on exegetical studies, the experience of receiving the Holy Spirit occurs after (not simultaneously - when) someone believes in the Lord Jesus. So, if we translate Acts 19:2a it will read like this, “And he [Paul] said to them [some of the disciples]: Have you all received the Holy Spirit, [after] you truly believed?Keywords: Exegesis, Receive the Holy Spirit, When, Believe.